Study of the diradicaloid character in a prototypical pancake-bonded dimer: the stacked tetracyanoethylene (TCNE) anion dimer and the neutral K2TCNE2 complex - Cui, Zhong-hua; Lischka, Hans; Müller, Thomas; Plasser, Felix; Kertesz, Miklos (ChemPhysChem, 2014)
The π-bonded tetracyanoethylene anion dimer (TCNE22−) and the neutral K2TCNE2 system have been investigated to obtain new insights into the unique features of two-electron multicenter (2e-mc) π-pancake bonding. The inter-radical interaction leads to a significant diradicaloid character described by two singly occupied molecular orbitals (SOMOs) of the monomers. A highly correlated approach, the multireference averaged quadratic coupled-cluster (MR-AQCC) method, has been used to achieve a balanced description of the different types of electron correlation that occur in this system. The analysis of the interaction energies for the two systems in the singlet and the lowest triplet states and of the unpaired electron densities demonstrate the importance of diradical π bonding in addition to the conventional van der Waals interactions that occur in intermolecular interactions. In this analysis, the separation of the repulsive Coulomb interaction energies from the remaining terms turned out to be a crucial prerequisite to achieve consistent results. Our calculations also confirm that the driving force behind the energetic stability of the pancake bonds predominantly derives from the overlap of the SOMO-SOMO bonding interaction.